Mobile ambulance dispatch and patient monitoring system - Pyi Thein Kyaw (Nanyang Technological University, 2023)
Due to a lack of resources, resource allocation has always been problematic. Some of the various resources that are scarce include time, money, labour, tools, land, and raw materials. Similar resource allocation issues are present in the Emergency Medical System at the moment. The operation of transporting patients from accident sites to hospitals should not be hampered by the allocation of scarce resources, including ambulances, drivers, and paramedics. The aim of this report is to offer more in-depth details and a solution regarding the distribution of resources in the emergency medical system. The author of this final year project integrates software in order to create a web application for the emergency medical services system. With the best solution based on the severity of the patients at each location, this web application would help in the efficient calculation and allocation of support to respective accident locations and to safely transport patients to the nearest hospitals in the quickest possible time, so that patients can receive the medical care support.